Variasi Pelafalan Bunyi Afrikat Bahasa Jepang oleh Penutur Berlatar Belakang Bahasa Bali - Candra Lestari, Ni Putu; Suparwa, I Nyoman; Simpen, I Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 25 No 1 (2018): MaretDO - 10.24843/ling.2018.v25.i01.p07, 2018)
This study aims to analyze Japanese affricates sound variation pronunced by Japanese speaking of Balinese. Variation of pronunciation were analyzed by using theory of generative phonology with accoustic phonetic. Kind of affricates sound variation by Japanese speaker of Balinese are alveolar affricates [t s ] and [d z ]. Voiceless alveolar affricates [t s ] is variated in three varians, such as voiceless alveolar fricative [s] and voiceless palatal affricates [ç], and voiceless alveolar affricates [t s ] i.e. words tsuki ‘moon’ , atsui ‘hot’, dan matsu ‘wait’. Voiced alveolar affricate [d z ] is variated in three varians, such as voiceless alveolar fricative [s] and voiced palatal-alveolar affricate [?], and voiced alveolar fricative [z] i.e. words zannen ‘a pity, zenzen ‘nothing at all’, douzo ‘please’.This variation are caused by the characteristic changed in place of articulation and manner of articulation by Japanese speaker of Balinese. Manner of articulation of alveolar affricate [t s , d z ] was approached by fricative manner [s] of articulation in Balinese. Place of alveolar affricate articulation changing to palatal [ç] and alveopalatal [?] approached to sound in Balinese. The variation on alveolar fricative level is reached by basic learner, affricate level is reached by intermediate learner, and advanced learner pronounced approximately similar with the native speaker has